PENGGUNAAN BAHASA TONSEA PADA KALANGAN REMAJA DESA TANAH PUTIH KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Boston Situmorang (Universitas Sam Ratulangi, 2023)
Humans are social creatures who interact with others in meeting various needs of life. Therefore, humans are inseparable from interacting using language as a means of communication. Language is a social communication tool in the form of a system of sound symbols produced from human speech. Language is an important element in influencing human life and culture. One of the languages that must be maintained and protected is the regional language. Regional languages are languages that are one of the criteria for identifying an ethnic group or ethnic group. Regional languages as a means of communication in the community must certainly be maintained and preserved in the community, so that the criteria for identification in tribes and regions are not lost. Teenagers in Tanah Putih Village mostly speak less and less Tonsea. However, most of the teenagers who interact use Manadonese Malay in their daily lives, but other teenagers also use Tonsea to interact with their own parents. The role of parents in teaching Tonsea language is very beneficial for teenagers today because parental education greatly influences children to use their respective regional languages. The role of parents to use the Tonsea language in interacting is applied in everyday life. With that, the Tonsea language is still always used in everyday life. Keywords: teenager, communication, Tonsea language